PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE 360-DEGREE FEEDBACK: Studi Kasus: PT. Satria Manunggal Petrolindo - Rahadi, Dedi Rianto; Fauzi, Rahmat; Saputra, Zaky (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
The purpose of this evaluation study is related to the work of employees of PT Satria Manunggal Petrolindo. Surveys are one of the most important evaluation factors related to the improvement of efficiency and quality aimed at the realization of the business goals and objectives of the company, whereas traditional evaluation methods were used in employee evaluation. The evaluation method used causes discomfort in some employees and weakens motivation, which affects the productivity of employees. To solve these problems, a study was conducted on the performance of employees of PT Satria Manunggal Petrolindo. The company uses the 360-degree feedback method as a measurement method for staff evaluation. This method uses comprehensive feedback from all levels of the employee to evaluate work behavior, consisting of five evaluation components: self-evaluation, supervisor evaluation, peer evaluation, subordinate evaluation manager (SAM), and client/customer evaluation. The result of the research and evaluation of the problems of this work is the use of the 360-degree feedback method in evaluating the work results of employees. Applying the 360-degree feedback method to personal evaluation is one method that provides objective evaluations. The final results obtained in the evaluation process are considered by the management of the company when making decisions regarding the future of the employees and the company. Employees can also increase their comfort and motivation to work with PT. Satria Manunggal Petrolindo, which ultimately affects the improvement of the company's efficiency and the achievement of business goals.